2013
DOI: 10.1186/1745-6215-14-356
|View full text |Cite|
|
Sign up to set email alerts
|

The Multi Centre Canadian Acellular Dermal Matrix Trial (MCCAT): study protocol for a randomized controlled trial in implant-based breast reconstruction

Abstract: BackgroundThe two-stage tissue expander/implant (TE/I) reconstruction is currently the gold standard method of implant-based immediate breast reconstruction in North America. Recently, however, there have been numerous case series describing the use of one-stage direct to implant reconstruction with the aid of acellular dermal matrix (ADM). In order to rigorously investigate the novel application of ADM in one-stage implant reconstruction, we are currently conducting a multicentre randomized controlled trial (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Proponents to this approach have noted it to be cost-effective, to be safe, and to have a reasonable complication profile. 14 16 A current ongoing randomized trial comparing BREAST-Q and other outcomes between single-stage and 2-stage ADM breast reconstruction 17 should provide additional high level of evidence data to the current ADM breast reconstruction literature. Another area of recent interest in the literature is the use of terminally sterile ADMs, which may help mitigate the higher complication rates that ADM confers on breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Proponents to this approach have noted it to be cost-effective, to be safe, and to have a reasonable complication profile. 14 16 A current ongoing randomized trial comparing BREAST-Q and other outcomes between single-stage and 2-stage ADM breast reconstruction 17 should provide additional high level of evidence data to the current ADM breast reconstruction literature. Another area of recent interest in the literature is the use of terminally sterile ADMs, which may help mitigate the higher complication rates that ADM confers on breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to highlight the positive responses to the questions in the physical well-being domain, as more physical symptom complaints were expected after the surgical procedure. In 2013, Eltahir et al 30 . assessed the quality of life of women following breast reconstruction in comparison with those of patients who underwent mastectomy, using the BREAST-Q ® questionnaire, and observed that women showed less pain and fewer limitations after reconstruction (p = 0.007).…”
Section: Discussionmentioning
confidence: 99%
“…Out of the few relevant articles, the Zhong et al study is an ongoing protocol with no established results 18 , while another article by Dikmans et al studied one-stage vs. two-stage approaches but did not use quality of life as a primary endpoint 19 . The only suitable randomized controlled trial (RCT) selected for critical appraisal, entitled "Quality of life and patient satisfaction after one-stage implant-based breast reconstruction with an acellular dermal matrix versus two-stage breast reconstruction (BRIOS): primary outcome of a randomised, controlled trial" 20 , studies the clinical question of interest and also uses quality of life as a primary endpoint.…”
Section: Related Literaturementioning
confidence: 99%